Determinants of capital structure: an empirical study of firms in Iran. Issue 1 (9th February 2015) - Alipour, Mohammad; Mohammadi, Mir Farhad Seddigh; Derakhshan, Hojjatollah
Abstract : Purpose: – This paper aims to investigate the determinants of capital structure of non-financial firms in Iran. Design/methodology/approach: – This paper reviews different conditional theories of capital structure to formulate testable propositions concerning the determinants of capital structure of Iranian companies. Pooled ordinary least squares and panel econometric techniques such as fixed effects and random effects are used to investigate the most significant factors that affect the capital structure choice of manufacturing firms listed on Tehran Stock Exchange Iran during 2003-2007. Findings: – The results of the study suggest that variables such as firm's size, financial flexibility, asset structure, profitability, liquidity, growth, risk and state ownership affect all measures of capital structure of Iranian corporations. Short-term debt is found to represent an important financing source for corporations in Iran. The results of the present research are consistent with some capital structure theories. Research limitations/implications: – In general, the results provide evidence that the five theories discussed influence emerging markets. Due to the existence of a negative relationship between profitability and capital structure, investors must consider capital structure before making investment decisions. Practical implications: – This study has laid some groundwork to explore the determinants of capital structure of Iranian firms upon which a more detailed evaluation could be based. Furthermore, the empirical findings will help corporate managers in making optimal capital structure decisions. Originality/value: – To the authors' knowledge, this is the first study that explores the determinants of capital structure of manufacturing firms in Iran by using the most recent data. Moreover, this paper provides a theoretical model to explain the mechanism of how the ownership structure impacts debt financing.